DEVELOPING AN INTERPROFESSIONAL STUNTING PREVENTION MODULE: AN EDUCATIONAL DESIGN RESEARCH STUDY - Handoko, Erwin; Sinaga, Nelly Dameria; Sagala, Martha Sutriska; Wahyu, Afnizar; Purba, Jhon Roby; Silaban, Ribka Narwastu; Nainggolan, Yanti Maria; Pratama, Irza Haicha; Rosmiati, Risti; Manalu, Putranto (Universitas Gadjah Mada, 2026)
ABSTRACTBackground: Stunting is a major public health issue in Indonesia, with a prevalence rate of 19.8%. Addressing this challenge requires coordinated action across multiple health disciplines, yet educational resources to promote interprofessional collaboration in stunting prevention remain limited. Aims: To develop an interprofessional education (IPE) module for undergraduate students across five health-related disciplines - medicine, nursing, midwifery, nutrition, and physiotherapy - and evaluate its effectiveness.Methods: Using an Educational Design Research, the study developed and tested the module through an iterative process. Participants' knowledge and collaboration readiness were assessed using pre- and post-tests and the Readiness for Interprofessional Learning Scale (RIPLS). Results: Wilcoxon signed-rank tests showed that the IPE module significantly improved students' knowledge about stunting prevention (p < .001, Z = 4.239, r = .80) and readiness for interprofessional collaboration (p = .016, Z = 2.409, r = .46). Thematic analysis of student reflections revealed improved understanding of the roles and contributions of different health professions, better awareness of the value of interdisciplinary collaboration, and an appreciation for community engagement in stunting prevention. Challenges identified included interpersonal and communication issues, time constraints, and overlapping responsibilities among professions. They also provided suggestions for module improvement, such as involving more programs from health and nonhealth disciplines and enhancing content depth. Conclusion: The study's findings suggest that IPE is an effective tool for equipping future healthcare professionals to address complex health issues such as stunting, and that the approach should be expanded and refined for broader application in health education.